Use of gas chromatography mass spectrometry to elucidate metabolites predicting the phenotypes of IgA nephropathy in hyper IgA mice. - Makoto Kurano; Yutaka Yatomi (PLoS ONE, 2019)
IgA nephropathy, a common chronic kidney disease, has various possible outcomes. Therefore, the identification of novel prognostic biomarkers is needed. To this purpose, we used gas chromatography mass spectrometry to search for metabolites capable of predicting the phenotypes of IgA nephropathy in hyper IgA (HIGA) mice, an established model mice for IgA nephropathy. We measured the plasma metabolite levels in 12- and 22-week-old mice, prior to the manifestation of IgA nephropathy phenotypes, and statistically investigated the associations between these metabolites and the phenotypes of IgA nephropathy, such as the urine protein levels and histological phenotypes of the kidney at 32 weeks. We observed that in plasma samples collected from 12- and 22-week-old HIGA mice, the urinary protein levels were significantly associated with 8 and 10 metabolites, the glomerular cellular component levels were significantly associated with 8 and 7 metabolites, and the mesangial substrate levels were significantly associated with 8 and 8 metabolites, respectively. Among the candidate metabolites associated with the phenotypes of IgA nephropathy, coniferyl alcohol levels were significantly higher in HIGA mice at all of the 12, 22, and 32 weeks of age. Since this study was an observational study, we could not elucidate the underlying mechanisms; however, we were able to identify new candidate metabolites, such as coniferyl alcohol, as being potentially involved in the pathogenesis of IgA nephropathy. These results might help to develop novel laboratory tests and therapeutic reagents for IgA nephropathy in the future.